Reducing Tantrum Behavior In Autistic Children Through “Isolationary Time-Out” Type Of Time Out Techniques - Mirnawati Mirnawati; Amka Amka (STAI Hubbulwathan Duri, 2022)
This study aims to determine the effectiveness of the